Association of alcohol consumption and dietary patterns in the adult population: data from the ESSE-RF study - N. S. Karamnova; A. I. Rytova; O. B. Shvabskaya; S. A. Shalnova; S. A. Maksimov; Yu. A. Balanova; S. E. Evstifeeva; A. E. Imaeva; A. V. Kapustina; G. A. Muromtseva; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
The alcohol consumption is associated with dietary patterns.  Aim. To study the associations of alcohol consumption and dietary patterns in the adult population.  Material and methods. The analysis was carried out using representative samples of male and female population aged 25-64 years (n=19437; men, 7306; women, 12131 women) from 13 Russian regions.The response rate was 80%. We assessed nutrition by the frequency of consuming basic food groups. The low alcohol intake (LI) category includes women and men who consume <42 g and <84 g, moderate consumption (MI) — 42 g and 84 g, high intake (HI) — 84 g and 168 g ethanol per week, respectively.Results. In comparison with men who do not drink alcohol, MI and HI category representatives more often consume red meat — by 22 and 36%, meat and sausages — by 37 and 48%, and less often: fish products — by 34 and 33%, cottage cheese — by 51 and 53%, respectively. More rare consumption of poultry is significant in the MI group, vegetables/fruits — in the HI group, sweets — in the LI group. Consumption of pickles, cereals, pasta, liquid dairy products, cheese and sour cream does not differ between the groups in men. Compared to women who do not drink alcohol, women in the LI, MI and HI groups significantly more often consume meat and sausages — by 16, 28 and 85%, respectively. Women of the LI and MI groups more often consume red meat — by 15 and 33%, confectionery — by 29 and 24%, less often: cereals — by 9 and 18%, legumes — by 44 and 53% and cottage cheese — by 19 and 44 %, respectively. Women of the LI category more often daily consume milk, kefir and yogurt — by 26%, and less often fish products — by 18%. Women of the HI group are less likely to consume fruits/vegetables. Consumption of poultry, pickles and cheese do not differ between groups among women.Conclusion. People who consume alcoholic beverages have a pronounced nutritional imbalance, characterized by a higher consumption of red meat, especially processed, high-fat dairy products, salt, and in women, confectionery.